Key elements for contraceptive interventions in Ralámuli adolescents from urban settlements in Chihuahua - Carrillo-Castro, Bertha Alicia; Orozco-Gómez, Claudia; Pelcastre-Villafuerte, Blanca Estela (Horizonte Sanitario, 2025)
Objective: Describe the key elements for designing interventions to promote the use of contraceptive methods among Ralámuli adolescents living in urban settlements in Chihuahua, based on their experiences, needs, and specific cultural contexts.Material and methods: Qualitative design study, a focus group was carried out that included six indigenous female adolescents, between 12 and 19 years of age, from an indigenous settlement in the city of Chihuahua, the selection of participants was intentional by criteria, the data collected through the focus group were recorded and transcribed manually and analyzed with a content qualitative analysis perspective.Results: Indigenous adolescents expressed to know about the most common contraceptive methods, condom, pills and implant. Seven categories and three subcategories were established: use, experience, parents' opinion, negotiation, need for knowledge, importance of sexual relations and promotion strategies.Conclusions: Ralámuli adolescents use contraceptive methods; it is necessary that the development of interventions be culturally appropriate and that they be educated on topics that allow them to negotiate, maintain safe relationships, and about the use of contraceptive methods.